New taxa and notes of some described species of Agraeciini (Orthoptera: Tettigoniidae: Conocephalinae) from Malay Peninsula - Tan, Ming Kai; Ingrisch, Sigfrid (Zootaxa, 2014)
Four new species from three genera of Agraeciini from Malay Peninsula are described: Paragraecia temasek sp. n., Peracca mirzai sp. n., Peracca macritchiensis sp. n. from Singapore, and Lichnofugia malaya sp. n. from Peninsular Malaysia. The first records and descriptions of the female of Liara alata Ingrisch, 1998 and the male of Paragraecia gracilis Ingrisch, 1998 are given.